An assessment of the barriers to accessing the Basic Package of Health Services (BPHS) in Afghanistan: was the BPHS a success?. Issue 1 (December 2016) - Frost, Alexandra; Wilkinson, Matthew; Boyle, Peter; Patel, Preeti; Sullivan, Richard
Abstract Afghanistan is one of the most fragile and conflict-affected countries in the world. It has experienced almost uninterrupted conflict for the last thirty years, with the present conflict now lasting over a decade. With no history of a functioning healthcare system, the creation of the Basic Package of Health Services (BPHS) in 2003 was a response to Afghanistan's dire health needs following decades of war. Its objective was to provide a bare minimum of essential health services, which could be scaled up rapidly through contracting mechanisms with Non-Governmental Organisations (NGOs). The central thesis of this article is that, despite the good intentions of the BPHS, not enough has been done to overcome the barriers to accessing its services. This analysis, enabled through a review of the existing literature, identifies and categorises these barriers into the three access dimensions of: acceptability, affordability and availability. As each of these is explored individually, analysis will show the extent to which these barriers to access are a critical issue, consider the underlying reasons for their existence and evaluate the efforts to overcome these barriers. Understanding these barriers and the policies that have been implemented to address them is critical to the future of health system strengthening in Afghanistan.